ETHICAL TEACHINGS OF AL-FARABI AND YUSUP BALASAGUNI IN THE CONTEXT OF THE HISTORY OF NOMADISM (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article affirms the well-known truth that the past is the key to a correct understanding of the present. Modern social relations are undoubtedly based on the positive social experience of the past and on rational comprehension of it. To preserve and develop the experience of ancestors, including the invaluable ethical heritage of Al-Farabi, Yusuf Balasaguni in the context of philosophical reconstruction, the original history of nomadism is an indisputable task of modern modern Kyrgyz science.
Keywords: Al-Farabi, Yusuf Balasaguni, person, society, state, philosophy, morality, ethics, knowledge, experience, nomadism.